Production, Characterization and Evaluation of Potential Applications of Bioemulsifier Produced by an Endophytic Actinomycete EARN5 isolated from Andrographis paniculata - K Rahi, Deepak; Urvashi, Urvashi (Research in Biotechnology, 2015)
A number of natural, synthetic, plant and animal derived emulsifiers are already been used at commercial level but some of the disadvantages and limitations with these available emulsifiers have forced researchers to search for suitable and feasible alternatives. Emulsifiers of microbial origin can solve the problem to a large extent and therefore there is a need to explore their possibilities on regular basis. In present investigation, the endophytic actinomycetes have been used to explore their potential of producing bioemulsifier is an important attempt in this regard. The isolation of endophytic actinomycetes were made from the tissues of different parts of medicinal plants which were obtained from the medicinal plant garden of Panjab University, Chandigarh, India. It resulted in isolation of a total of seven actinomycetes isolates. All of which were successfully isolated in to pure form and screened out for their potential to produce the bioemulsifier in maltose yeast extracts broth (MYEB). Isolate no. EARN5 which was identified as the species of Actinomycetes was found to exhibit the maximum emulsification activity with different oils and hydrocarbons used. There after the studies pertaining to optimization of various parameters to enhance the yield of the test bioemulsifier was also performed. The optimization of physical parameters revealed the maltose yeast extract as the best production medium, 7 days as the most suitable incubation period, 29Â±1Â°C as the optimum temperature, pH of 7 and 130 rpm as the optimum agitation speed. The biochemical parameters revealed the cellulose and yeast extract as the best sources of carbon and nitrogen respectively. The test bioemulsifier was also evaluated for the type of emulsion it formed and its stability. Besides, it was also characterized for various physical (solubility, SEM, critical micellar concentration and surface tension), molecular (FTIR and elemental analysis) and chemical properties (protein, carbohydrates and lipid contents). The test bioemulsifier was also evaluated for its efficiency to remove the oil from contaminated water and cream from full cream milk. The results obtained on the studies found to possess both the properties in the test bioemulsifier.